1998
DOI: 10.1021/es9803714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of California Reformulated Gasoline on Motor Vehicle Emissions. 1. Mass Emission Rates

Abstract: This paper addresses the impact of California phase 2 reformulated gasoline (RFG) on motor vehicle emissions. Phase 2 RFG was introduced in the San Francisco Bay Area in the first half of 1996, resulting in large changes to gasoline composition. Oxygen content increased from 0.2 to 2.0 wt%; and alkene, aromatic, benzene, and sulfur contents decreased. Gasoline density and T 50 and T 90 distillation temperatures also decreased. Light-duty vehicle emission rates were measured in a Bay Area roadway tunnel in summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 18 publications
(36 reference statements)
2
97
0
1
Order By: Relevance
“…Tunnel measurements have led to revisions of emission models, 286 determined the effect of reformulated gasoline on HC spp. emitted by vehicles, 287 and quantified carbonyl and PAH emissions.…”
Section: Emission Inventoriesmentioning
confidence: 99%
“…Tunnel measurements have led to revisions of emission models, 286 determined the effect of reformulated gasoline on HC spp. emitted by vehicles, 287 and quantified carbonyl and PAH emissions.…”
Section: Emission Inventoriesmentioning
confidence: 99%
“…At the time of these measurements, we estimated based on a license-plate survey that ~99% of vehicles in the center bore are gasoline-powered and >94% of the vehicles were originally outfitted with three-way catalyst systems (Kean et al, 2000). During the rush-hour period of measurement, driving conditions and the mean vehicle age (~6 years old) at the Caldecott Tunnel are consistent from year to year (Kirchstetter et al, 1999;Ban-Weiss et al, 2008).…”
Section: Light-duty Ammonia Emission Factor Trends Between 1999 and 2006mentioning
confidence: 99%
“…Although the effects of meteorology on the ozone concentrations have been greatly reduced, various factors in addition to CaRFG are responsible for changes in the emissions of ozone precursors. For example, Kirschtetter et al 3 found that both fleet turnover and CaRFG contributed to emission reductions during a multi-year tunnel study in the S.F. Bay Area.…”
Section: Attributing An Ozone-reducingmentioning
confidence: 99%
“…2 Specifications for CaRFG are given in Table 1. While others have studied changes in vehicle emissions 3 or in ambient levels of ozone precursors 4 before and after the introduction of CaRFG, the goal of this study was to determine whether an ozone-reducing effect could be attributed to CaRFG by comparing ambient ozone concentrations in 1996 to ozone concentrations in earlier years.…”
Section: Introductionmentioning
confidence: 99%